2022
DOI: 10.1111/1756-185x.14437
|View full text |Cite
|
Sign up to set email alerts
|

The association between hydroxychloroquine use and future development of systemic lupus erythematosus in patients with primary Sjögren's syndrome

Abstract: Aim Hydroxychloroquine (HCQ), commonly used to treat patients with primary Sjögren's syndrome (pSS), has been shown to delay the development of systemic lupus erythematosus (SLE). This study aimed to explore the association between HCQ use and future development of SLE in pSS patients based on a nationwide nested case–control study. Method Based on the National Health Insurance Research Database of Taiwan, those patients who were diagnosed with SLE at least 1 year after the diagnosis of pSS were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Nevertheless, in severe cases, early intervention is essential to prevent complications. 11 Uveitis is a type of intraocular inflammation that is commonly associated with autoimmune diseases, and is thought to result from an immune-mediated attack on the uveal tract. 7 The pathogenesis of uveitis in autoimmune diseases is believed to be multifactorial, involving genetic, environmental, and immune factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, in severe cases, early intervention is essential to prevent complications. 11 Uveitis is a type of intraocular inflammation that is commonly associated with autoimmune diseases, and is thought to result from an immune-mediated attack on the uveal tract. 7 The pathogenesis of uveitis in autoimmune diseases is believed to be multifactorial, involving genetic, environmental, and immune factors.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, topical corticosteroids are the primary treatment for managing uveitis. Nevertheless, in severe cases, early intervention is essential to prevent complications 11 . Uveitis is a type of intraocular inflammation that is commonly associated with autoimmune diseases, and is thought to result from an immune‐mediated attack on the uveal tract 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that HCQ can reduce disease activity, prevent disease flares, decrease the long-term need for glucocorticoids (GCs), and benefit pregnant women in SLE patients. Furthermore, HCQ has been reported to have multiple comprehensive effects, including anti-thrombotic, hypoglycemic, lipid-lowering, and reduced risk of cardiovascular disease 3 , 4 . More importantly, HCQ can lower the mortality rate in patients with SLE 5 .…”
Section: Introductionmentioning
confidence: 99%